Evaluating the academic achievement of graduate students working in the field of physical education from their point of view - Khudhair, Yasir; Hamdan, Abdullah; Fadhil, Maath (Journal of Physical Education, 2023)
The research aimed to prepare a measure to evaluate the academic achievement of graduates working in the field of physical education from their point of view, to identify the extent to which graduating students benefit from the curriculum of the College of Physical Education and Sports Sciences, University of Baghdad/Al-Jadriya, and to identify the impact of academic subjects in the practical and theoretical fields. The researchers used the descriptive approach in the research procedures as it is an appropriate approach in achieving the research objectives. The following questions are: What are the academic subjects that have the most impact on graduating students? What are the academic subjects that have the least impact on the areas of their lives after graduation, Of two axes, the first axis (15) paragraphs, the second axis (12) paragraphs. The research community included students from the College of Physical Education and Sports Sciences / University of Baghdad / Al-Jadriyah from the graduates. A 30% proportional random research sample was chosen, amounting to 110 male and female students, and the number of students in the fourth stage reached 2022 -2023 (362) male and female students.